Research on The Medical Education - Perales Cabrera, Alberto (1998)
The author reviews the impact of globalization on medical teaching. Regarding research teaching for medical undergraduates, he underlines that the important issue is to help the students to develop a research attitude and behavior for which he proposes the corresponding teaching strategies. He also points out the value of research activities in the organizational development of any School of Medicine for which at present remains with an actual survival role.